Production and characterization of monoclonal antibodies specific for canine CD138 (syndecan‐1) for nuclear medicine preclinical trials on spontaneous tumours. (14th April 2016) - Diab, M.; Nguyen, F.; Berthaud, M.; Maurel, C.; Gaschet, J.; Verger, E.; Ibisch, C.; Rousseau, C.; Chérel, M.; Abadie, J.; Davodeau, F.
Abstract: We isolated 11 antibodies specific for canine CD138 (cCD138) to validate the interest of CD138 antigen targeting in dogs with spontaneous mammary carcinoma. The affinity of the monoclonal antibodies in the nanomolar range is suitable for immunohistochemistry and nuclear medicine applications. Four distinct epitopes were recognized on cCD138 by this panel of antibodies. CD138 expression in canine healthy tissues is comparable to that reported in humans. CD138 is frequently expressed in canine mammary carcinomas corresponding to the human triple negative breast cancer subtype, with cytoplasmic and membranous expression. In canine diffuse large B‐cell lymphoma, CD138 expression is associated with the 'non‐germinal center' phenotype corresponding to the most aggressive subtype in humans. This homology of CD138 expression between dogs and humans confirms the relevance of tumour‐bearing dogs as spontaneous models for nuclear medicine applications, especially for the evaluation of new tumour targeting strategies for diagnosis by phenotypic imaging and radio‐immunotherapy.